Venezuelan migrants in Peru and their entrepreneurial intention during the Covid-19 pandemic - Villalobos Álvarez, Diego Leonardo (2022)
Objective: The article aims to understand the influence of how attitude (ATT), the perception of country support (PCS) for entrepreneurship, and entrepreneurship self-efficacy (ESE) support entrepreneurial intention (EI) among Venezuelan migrants living in Peru. Research Design & Methods: In total, 305 migrants from Venezuela living in Peru completed the online questionnaire. It contained 21 items that evaluated the variables to explain the EI. In the study, we employed the partial least squares structural equation modelling (PLS-SEM) technique. Findings: We found that ATT (0.591) and PCS for entrepreneurship (0.204) showed a direct and significant influence on ESE, while ESE showed a direct and significant influence (0.823) on the EI. The research model explained 67.7% of the EI. The analysis using bootstrapping technique showed the significance of the path coefficients. Implications & Recommendations: Current research showed the effect of ATT and PCS on ESE, which governments and organizations can use to create plans to promote entrepreneurship among migrants. Contribution & Value Added: Governments can use the study results to develop and improve new regulations to encourage entrepreneurship. The novelty of this study is the use of the PLS-SEM technique.